2020
DOI: 10.3390/s20174757
|View full text |Cite
|
Sign up to set email alerts
|

WiGAN: A WiFi Based Gesture Recognition System with GANs

Abstract: In recent years, a series of research experiments have been conducted on WiFi-based gesture recognition. However, current recognition systems are still facing the challenge of small samples and environmental dependence. To deal with the problem of performance degradation caused by these factors, we propose a WiFi-based gesture recognition system, WiGAN, which uses Generative Adversarial Network (GAN) to extract and generate gesture features. With GAN, WiGAN expands the data capacity to reduce time cost and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Another paper based on GAN is WiGAN [ 7 ], in which the authors showed that their proposed modelis environmental and user independent. First, the authors combined the structure of Deep Convolutional GAN [ 20 ] with the main characteristics of Conditional GAN [ 21 ].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Another paper based on GAN is WiGAN [ 7 ], in which the authors showed that their proposed modelis environmental and user independent. First, the authors combined the structure of Deep Convolutional GAN [ 20 ] with the main characteristics of Conditional GAN [ 21 ].…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, the authors of [ 7 ] proposed to add a data pre-processing module for the training deep learning model, whose main purpose was to convert raw CSI data into the sanitized CSI amplitude. This module consists of several data pre-processing steps, such as activity detection, interpolation, Discrete Wavelet Transform and sub-carrier selection.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations